The inexorable rise of Chimerica: The long-term scenario - Marcin Piatkowski (Transformation, Integration and Globalization Economic Research (TIGER), 2011)
The objective of this paper is to develop a scenario for the development of the world's economy, in which China and America become the two global economic hegemons, who dominate over other players, mainly including the EU, Japan and other BRICs, in a new multi polar world. For the purpose of this paper the two new superpowers will be called Chimerica.
Keywords: 330